Navigating Change: Exploring Self-Regulated Learning in Online Education at Higher Education Institutions - Mairi, Salam (J-SHMIC : Journal of English for Academic, 2025)
The shift to online learning due to the COVID-19 pandemic has brought new challenges and opportunities for students' learning processes. This qualitative study explores how Indonesian university students navigated self-regulated learning (SRL) during a fully online semester. Thematic analysis of the in-depth, semi-structured interviews with five participants revealed three key themes related to strategies for self-regulated learning in online environments, challenges in online learning, and support systems and external resources in online learning. Findings suggest that students took responsibility for their learning but faced challenges in motivation, time management, and well-being. It highlights the need for both autonomy and structured support. The study emphasizes the importance of cultivating SRL skills to improve online learning outcomes and providing structured support and SRL integration into curriculum design.